2018
DOI: 10.1016/j.compind.2018.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Using a classifier ensemble for proactive quality monitoring and control: The impact of the choice of classifiers types, selection criterion, and fusion process

Abstract: In recent times, the manufacturing processes are faced with many external or internal (the increase of customized product re-scheduling, process reliability,.. ) changes. Therefore, monitoring and quality management activities for these manufacturing processes are difficult. Thus, the managers need more proactive approaches to deal with this variability. In this study, a proactive quality monitoring and control approach based on classifiers to predict defect occurrences and provide optimal values for factors c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 64 publications
0
8
0
1
Order By: Relevance
“…Their model outperformed other prediction methods, such as a MLP and a regression tree, for the evaluation of two real data sets. Moreover, ensemble classier construction techniques were also studied by Thomas et al [45] for proactive quality monitoring and control. They employed four types of base classifiers for ensemble construction, i.e.…”
Section: Ensemble Classification and Feature Selection Techniquesmentioning
confidence: 99%
“…Their model outperformed other prediction methods, such as a MLP and a regression tree, for the evaluation of two real data sets. Moreover, ensemble classier construction techniques were also studied by Thomas et al [45] for proactive quality monitoring and control. They employed four types of base classifiers for ensemble construction, i.e.…”
Section: Ensemble Classification and Feature Selection Techniquesmentioning
confidence: 99%
“…Additionally, numerous methods have been proposed to select predictors from a set of previously trained models. (Thomas et al, 2018) reports that two such families of methods either perform a selection based solely on a performance score, for example the MSE, or perform a selection based on both a performance scores and a diversity score. However, when comparing two such methods on their industrial dataset, they found no significant advantage to the use of a diversity based method, compared to the use of a performance based method.…”
Section: Ensemble Selectionmentioning
confidence: 99%
“…Several researchers have adopted the idea of incorporating the general loss matrix into C4.5 decision tree algorithm to reduce the misclassification cost or to minimize the misclassification loss [31][32][33][34]. These algorithms introduced heuristic splitting methods that perform dual tasks.…”
Section: Proposed Zero-one Loss Function Pruning Algorithm Based On Lmentioning
confidence: 99%